AKSELERASI PENGEMBANGAN KUBE BERBASIS SOSIOPRENEUR UNTUK PENGUATAN KEMANDIRIAN DAN KEBERLANJUTAN EKONOMI LOKAL DI KECAMATAN KUOK, KABUPATEN KAMPAR - Frini Karina Andini; Yunandra; Bunga Chintia Utami; Encik Rania Olivia (Universitas Mataram, 2026)
Kelompok Usaha Bersama (KUBE) Kerupuk Lomang Ubi Bersinar Kuok in Kuok District, Kampar Regency, faces priority problems in the aspects of production and business management. From the production side, product quality has not yet been standardized due to the absence of Standard Operating Procedures (SOP), while the use of manual tools limits production capacity and makes it difficult to compete with other SMEs that are more modern. From the management side, KUBE is still run informally, without a proper financial recording system, and applies marketing strategies that only focus on local markets without utilizing digitalization. This community service program was carried out using a sociopreneurship and participatory empowerment approach. The implementation methods included technical production training (quality control, SOP preparation, and product certification assistance), facilitation of modern production equipment, training on business management and financial recording using applications, as well as training on digital marketing strategies and product branding. The activities were supported by multi-stakeholder collaboration, including the village government, sub-district authorities, and the University, while also involving students through the MBKM program. The results of the program showed significant improvements in production quality and capacity, the establishment of better-organized financial records, and the development of digital-based marketing strategies that expanded market access. The social impact was evident from the increased role of women as KUBE members who became more economically independent, while the economic impact was reflected in improved productivity, members’ income, and the competitiveness of products based on local potential.